2018
DOI: 10.1038/s41588-018-0254-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phagocytosis regulators using magnetic genome-wide CRISPR screens

Abstract: Summary Phagocytosis is required for a broad range of physiological functions, from pathogen defense to tissue homeostasis, but mechanisms required for phagocytosis of diverse substrates remain incompletely understood. Here, we develop a rapid magnet-based phenotypic screening strategy, and perform eight genome-wide CRISPR screens in human cells to identify genes regulating phagocytosis of distinct substrates. After validating select hits in focused mini-screens, orthogonal assays and primary human macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
167
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(178 citation statements)
references
References 63 publications
9
167
2
Order By: Relevance
“…Importantly, phagocytosis is the process responsible for the induction of the pro-to anti-phenotypical switch in MPs. While numerous studies investigated the mechanisms involved in the progression or inhibition of phagocytosis, how apoptotic cells attract MPs and how MPs recognize them is still unknown [10,14,15,50,51]. In our study, phagocytosis of LysM CRE :Nfix fl/fl MPs was not impaired compared to control cells.…”
Section: Discussioncontrasting
confidence: 43%
“…Importantly, phagocytosis is the process responsible for the induction of the pro-to anti-phenotypical switch in MPs. While numerous studies investigated the mechanisms involved in the progression or inhibition of phagocytosis, how apoptotic cells attract MPs and how MPs recognize them is still unknown [10,14,15,50,51]. In our study, phagocytosis of LysM CRE :Nfix fl/fl MPs was not impaired compared to control cells.…”
Section: Discussioncontrasting
confidence: 43%
“…Jakobsdottir et al () identified a rare missense (p.P155L) variant affecting the C‐Type Lectin‐like domain (CTLD) of TM2D3 as a risk allele for late‐onset Alzheimer's disease in an Icelandic population, and proposed that Amx/TM2D3 may contribute directly or indirectly to the γ‐secretase cleavage of Notch and APP, a hypothesis that needs to be tested biochemically. More recently, Haney et al () identified TM2D1–3 as phagocytosis regulators based on CRISPR‐based screens using human phagocytic cell lines and proposed that these proteins may be involved in Alzheimer's disease by regulating amyloid clearance in the brain. This hypothesis should also be tested by biochemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, this route is difficult, expensive, and time-consuming (Sugimura et al, 2017). Another approach is to edit fully differentiated macrophages, which has shown some functional success in the literature (Barkal et al, 2017;Haney et al, 2018), though this also has limitations. The approach is specific to macrophages, rather than allowing for flexible differentiation, and is limited by the lifespan of mature macrophages in culture.…”
Section: Discussionmentioning
confidence: 99%